Penentuan Kadar Total Flavonoid Pada Ekstrak Bunga Kenop (Gomphrena globosa L.) Dengan Metode Spektrofotometri UV-VIS - Cahyaningsih, Erna; Dewi , Ni Luh Kade Arman Anita; Yuda, Putu Era Sandhi Kusuma; Irlangga, I Gusti Ngurah Agustia Adi Surya Taksu (Usadha, 2025)
Flavonoids are phenolic compounds widely distributed in plants and are well known for their antioxidant activity, which plays an important role in preventing degenerative diseases. One plant with potential as a flavonoid source is the globe amaranth flower (Gomphrena globosa L.), which has been traditionally used and reported to exhibit various pharmacological activities. This study aimed to determine the total flavonoid content of globe amaranth flower extract grown in Bali. Extraction was carried out using the maceration method with 96% ethanol at a ratio of 1:10, followed by remaceration. Phytochemical screening was performed to identify the presence of flavonoids, while total flavonoid content was determined using UV-Vis spectrophotometry with quercetin as the standard. Phytochemical screening confirmed the presence of flavonoid compounds in the extract. The determination of total flavonoid content showed a maximum wavelength at 433 nm, with a regression equation of Y = 0.0778X + 0.0012 and a correlation coefficient (r) of 0.9982. The total flavonoid content obtained was 81.808 mgQE/100 g extract. In conclusion, the globe amaranth flower (Gomphrena globosa L.) is a promising natural source of flavonoids and has potential to be developed as a raw material for traditional medicine, particularly as a natural antioxidant.